Construction and Practice of Primary School Research-based Learning Practice System from the Perspective of Core Literacy——Taking the Three Colors and Three Stages Research Learning Model of Harbin Jihong Primary School as an Example - Yingnan Liu (Education Research on Study Tours and Practice, 2026)
Under the backdrop of the new eras basic education reform, study trips, as a crucial vehicle for comprehensive practical activities, are undergoing a transformation from travel without learning to research and collaborative learning. This paper takes Harbin Jihong Primary School as the research subject. Based on the 2016 Opinions on Promoting Study Trips for Primary and Secondary School Students issued by the Ministry of Education and ten other ministries, along with subsequent relevant policy documents, and considering the context of high-quality educational development in 2026, it explores how to establish a systematic, scientific, and school-based study trip curriculum system using Broussonetia papyrifera. Through literature analysis, action research, and case study methods, the research constructs a practical model featuring a three-color red, blue, gold curriculum framework and a three-phase pre-, during, post- closed-loop management. Practice demonstrates that this system effectively addresses issues such as fragmented study trip resources, vague curriculum objectives, and simplistic evaluations, significantly enhancing students social responsibility, innovative spirit, and practical abilities. It provides a replicable paradigm for the high-quality development of regional study trip education.